The effect of ultrasonic tip working length on fluid dynamics in the root canal during the irrigation procedure: a computational fluid dynamics study - Weihan Wu; Yuxuan Chen; Chunshi Tong; Bohua Li; Xin Ma (BMC Oral Health)
Abstract Background Root canal irrigation is essential for infection control during root canal treatment. Ultrasonic irrigation is a common method of root canal irrigation used in the clinical practice; however, the working length of ultrasonic tip can influence the fluid dynamics of the irrigant. Different from previous studies which often utilized simplified models, this study aims to utilize the computational fluid dynamic (CFD) and finite element method to evaluate the flow dynamics characteristics of the irrigation fluid when the ultrasonic tip was placed at different depths in the root canal and to predict crack extension during ultrasonic cleaning, based on the real tooth model. Methods Images of the mandibular first premolar teeth were scanned using cone beam computed tomography (CBCT), and then imported into the software for three-dimensional reconstruction. ICEM CFD 18.0 software was used to establish the root canal irrigation. The ultrasonic working tip was positioned at distances from the apex stop of 1 mm, 1.5 mm, 2 mm, 2.5 mm, and 3 mm (i.e., the five different working lengths of the working tip are 10 mm, 9.5 mm, 9 mm, 8.5 mm, and 8 mm) respectively. Irrigation velocity, wall shear stress and volume fraction in the root canal were visualized after setting the computing conditions. A dentin microcrack model was established by ABAQUS 6.14 software to predict crack extension during ultrasonic cleaning. Results The CFD analysis showed that increasing the work length of the ultrasonic tip significantly increased vapor volume fraction, and wall shear stress, while reducing apical pressure. Notably, despite changes in the placement of the ultrasonic working tip, the velocity of irrigant always gradually decreases within the area 1 mm in front of the working tip. The pressure on the root canal significantly lower than the ultimate tensile strength of dentin. Conclusion Increasing the working length can influence vapor volume fraction, wall shear stress and apical pressure. The pressure on the root canal does not cause the dentin microcrack propagation, in order to provide a reference for clinical application.